Vulnerability of women in Jean Rhys’ selected novels - Faja, Hiba Meteab; Ruzy Suliza Hashim (Penerbit Universiti Kebangsaan Malaysia, 2021)
The female characters in Jean Rhys' two books, Quartet and Wide Sargasso Sea, are examined in this article. Rhys was born in Dominica but lived the remainder of her adult life in the United Kingdom; her unusual life experience, which incorporates English and Caribbean landscapes, resulted in literary works that represent women and men caught up in their lives' surroundings due to their pronounced cultural, social, and economic differences. Gender and psychological viewpoints have dominated Rhys scholarship; however, studies on vulnerability remain a vacuum that needs to be filled. Rhys' loneliness, existentialist outlook, and complex subjectivity are reflected in her novels, with her characters' troubled lives highlighted by feelings of emotional and physical estrangement. We can infer Rhys' characters' subjectivity due to migration and colonial culture by categorizing the causes and consequences of vulnerability.